Erfolgreiche Vertragskonzepte oder foedera incerta? - Selvaggi, Rocco (2020)
The present study deals with the foreign policy of the Western Roman Empire towards those Germanic tribes that were able to form sovereign states on Roman soil in connection with the fall of Western Rome: the Burgundians, the Vandals, the Suebi and the Visigoths. The central object of investigation is the international legal relations between the Empire and the various gentes in the 5th century. A collection of the West Roman-Germanic treaties - together with a presentation of their historical background - provides a sufficient overview of the political attitude of the Western Empire towards the Germanic peoples in the final phase of its disintegration process. Is there a certain "red thread" in West Rome's foreign policy?...